2020
DOI: 10.3390/agronomy10060864
|View full text |Cite
|
Sign up to set email alerts
|

NaCl and Na2SO4 Salinities Have Different Impact on Photosynthesis and Yield-Related Parameters in Rice (Oryza sativa L.)

Abstract: To elucidate the comparative effect of chloride and sulfate salinities on photosynthesis and yield components in rice, plants of Oryza sativa (cv. I Kong Pao (salt-sensitive)) were exposed in nutrient solutions to 20 mM Na2SO4 or 40 mM NaCl (electrical conductivity of c.a. 4.30 dS m−1 for both solutions) from seedlings to maturity stage. Both types of salt induced a strong decrease in net photosynthesis (AN) at the seedling and tillering stages, while the intercellular CO2 concentrations (Ci) remained unaffect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
3
11
0
1
Order By: Relevance
“…In contrast, Ls was signi cantly higher than that of the control (Fig. 4-7), which is consistent with the results of previous studies [43][44][45] . The decrease of Ci and the increase of Li and the simultaneous decrease of Pn and Gs are thought to lead to the decrease of photosynthetic rate through stomatal limitation 46,47 , which because salt stress causes physiological drought in plants.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Ls was signi cantly higher than that of the control (Fig. 4-7), which is consistent with the results of previous studies [43][44][45] . The decrease of Ci and the increase of Li and the simultaneous decrease of Pn and Gs are thought to lead to the decrease of photosynthetic rate through stomatal limitation 46,47 , which because salt stress causes physiological drought in plants.…”
Section: Discussionsupporting
confidence: 92%
“…Seeds of all 20 oat genotypes were germinated in hydroponics using Hoagland nutrient solution (Hoagland & Arnon, 1938) with seven different salinity levels. Since, actual field salinity is resultant of accumulation of various salt ions mixture (Bai et al, 2018;Irakoze et al 2020;Vargas et al 2018), therefore to mimic saline field condition in pots and hydroponic media, we used mixture of NaCl and Na 2 SO 4 in our study. Both NaCl and Na 2 SO 4 salts were mixed in equimolar ratio in such a way that the resultant solutions were of 0, 60, 80, 100, 120, 140 and 160 mM concentrations.…”
Section: Experiments 1: Seed Germination Studiesmentioning
confidence: 99%
“…It is considered as the major abiotic factor that limits plant productivity and agricultural yield [1,2]. Several studies have reported that salts present in soil and in irrigation water reduce plant growth [3][4][5][6][7][8][9][10] and consequently reduce crop production. Soil salinity affects plant growth, either through osmotic effects or ionic toxicity effects.…”
Section: Introductionmentioning
confidence: 99%